Investigating the Aerodynamic Surface Roughness Length over Baghdad City Utilizing Remote Sensing and GIS Techniques (Baghdad Science Journal, 2021)
This study calculated the surface roughness length (Zo), zero-displacement length (Zd) and height of the roughness elements (ZH) using GIS applications. The practical benefit of this study is to classify the development of Baghdad, choose the appropriate places for installing wind turbines, improve urban planning, find rates of turbulence, pollution and others. The surface roughness length (Zo) of Baghdad city was estimated based on the data of the wind speed obtained from an automatic weather station installed at Al-Mustansiriyah University, the data of the satellite images digital elevation model (DEM), and the digital surface model (DSM), utilizing Remote Sensing Techniques. The study area was divided into 15 municipalities (Rasheed, Mansour, Shulaa, Karrada, Shaab, Adhamiyah, Sadre 2, Sadre 1, Rusafa, Alghadeer, Baghdad Aljadeedah, Karkh, Kadhumiya, Green zone, and Dora). The results indicated that the variations in Zo depend strongly on zero-displacement length (Zd) and the roughness element height (ZH) and wind speed. The research results demonstrated that Baghdad Aljadeedah has the largest (Zo) with 0.43 m and Rasheed has the lowest value of (Zo) with 0.19 m.; the average (Zo) of Baghdad city was 0.32 m.